Processing Methodology and Dialectological Aspects of the Dictionary of Moravian and Silesian Anoikonyms (Minor Place Names) - Čižmárová, Libuše (Slavia Centralis, 2020)
This paper presents the routines used by Brno linguists working on the Dictionary of Moravian and Silesian Anoikonyms (preparing collective entries introduced by abstract headwords). The output will be primarily a multifunctional interactive digital dictionary. Since most of the material has been recorded in dialect form, the authors must be experienced in dialectology. The computer program offers the possibility to generate maps enabling comparison with dialectological maps of the Czech Linguistic Atlas.